2019
DOI: 10.1101/708578
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How well do crop modeling groups predict wheat phenology, given calibration data from the target population?

Abstract: 1 15 ABSTRACT 16 Plant phenology, which describes the timing of plant development, is a major aspect of 17 plant response to environment and for crops, a major determinant of yield. Many studies have 18 focused on comparing model equations for describing how phenology responds to climate but 19 the effect of crop model calibration, also important for determining model performance, has 20 received much less attention. The objectives here were to obtain a rigorous evaluation of 21 prediction capability of w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…ensemble of users within ensemble of models) cannot be regarded as the solution to estimate uncertainty due to parameterization (Confalonieri et al, 2016). As well, different calibration techniques do not seem to be primarily responsible for differences in model performance (Wallach et al, 2020) and the contribution of the initialization to the uncertainty in SOC changes can be negligible compared to the uncertainty related to the model itself and simulated systems characteristics (Dimassi et al, 2018). As uncertainty could not be associated with any individual simulation, we focussed on the analysis of model residuals.…”
Section: Multi-model and Ensemble Assessmentmentioning
confidence: 99%
“…ensemble of users within ensemble of models) cannot be regarded as the solution to estimate uncertainty due to parameterization (Confalonieri et al, 2016). As well, different calibration techniques do not seem to be primarily responsible for differences in model performance (Wallach et al, 2020) and the contribution of the initialization to the uncertainty in SOC changes can be negligible compared to the uncertainty related to the model itself and simulated systems characteristics (Dimassi et al, 2018). As uncertainty could not be associated with any individual simulation, we focussed on the analysis of model residuals.…”
Section: Multi-model and Ensemble Assessmentmentioning
confidence: 99%
“…The results here show that phenology predictive performance for the calibration environments is significantly correlated with predictive performance for new environments. This was also found to be the case for a study evaluating phenology prediction by modeling groups based on phenology in French environments (Wallach et al, 2019) and suggests that in these cases, it may be worthwhile to use performance-weighted model ensembles. This may be due to the fact that in these studies, the calibration and evaluation environments were similar to one another.…”
Section: Model Averagingmentioning
confidence: 68%
“…The within-structure standard deviation here is 4.3 days, compared to a between-structure standard deviation (contribution of structure) of 11.9 days. The study based on French environments found a within-structure standard deviation of 5.6 days and a betweenstructure standard deviation of 8.0 days (Wallach et al, 2019). Confalonieri et al (2016) also found that the within-structure effect was in general, but not in all cases, smaller than the between-structure effect on variability.…”
Section: Sources Of Variabilitymentioning
confidence: 91%
See 1 more Smart Citation
“…These can be stand-alone temperature (and sometimes photoperiod) driven phenology models, such as DD10 for rice [17,18] or more complex crop growth simulation models such as APSIM [19] or ORYZA [20]. These models are particularly useful to assess the expected crop response to changes in the environment or management, but in practice they do not always perform well due to the insufficient empirical data available for calibration [21], and a limited ability to capture the effects of extreme weather events on crop phenology [22][23][24]. Moreover, the use of these models can be overly simplistic if differences in the environment, variety and other crop managements are insufficiently represented [15,25].…”
Section: Introductionmentioning
confidence: 99%